2020
DOI: 10.5424/sjar/2020183-16113
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of carcass characteristics, meat quality and nutrition value in Iberian wild red deer

Abstract: Aim of study: The effects of hunting season (autumn vs. winter) on carcass characteristics and meat quality of Iberian wild red deer were assessed.Area of study: A total of 100 males of wild red deer of Iberian genetic line (Cervus elaphus) were hunted on Ciudad Real (south central Spain).Material and methods: Yields for shoulder (with bone), neck, backbone, loin, tenderloin, leg (with bone), short plate and flank were determined. In addition, samples of Longissimus thoracis et lumborum and Rectus abdominis mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The medium concentrations of Cu for red deer and wild boar measured 1.9 and 2.2 mg/kg, respectively. The Cu content in red deer agrees with findings in previous studies where levels were reported as 1.5 mg/kg [38] and 2.0 mg/kg [16]. In another deer species, fallow deer, Cawthorn et al [29] found Cu levels that ranged between 1.94 and 2.01 mg/kg.…”
Section: Coppersupporting
confidence: 89%
“…The medium concentrations of Cu for red deer and wild boar measured 1.9 and 2.2 mg/kg, respectively. The Cu content in red deer agrees with findings in previous studies where levels were reported as 1.5 mg/kg [38] and 2.0 mg/kg [16]. In another deer species, fallow deer, Cawthorn et al [29] found Cu levels that ranged between 1.94 and 2.01 mg/kg.…”
Section: Coppersupporting
confidence: 89%
“…It is also worth noting that deer meat has excellent nutritional characteristics. This meat has low fat and cholesterol contents and high amounts of protein, essential amino acids and minerals [21,[23][24][25][26]. Additionally, the fatty acids profile of the deer meat is characterized by high amounts of PUFA (43.80 g/100 g total fatty acids) and long-chain n-3 [9,[24][25][26], which have positive effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the consumption of both fresh meat and traditional meat products elaborated with game meat has increased [ 1 ]. It is due to their particular taste and excellent nutritional characteristics (low fat and cholesterol contents and high amounts of other essential nutrients) [ 2 , 5 , 6 , 7 , 8 ]. Additionally, taking into account health aspects, it also has high amount of PUFA (39–50 g/100 g fatty acids) [ 8 ] and long-chain n-3 fatty acids [ 2 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%